Waveguide quantum electrodynamics at the onset of spin-spin correlations - Sebastián Roca-Jerat; Marcos Rubín-Osanz; Mark D. Jenkins; Agustín Camón; Pablo J. Alonso; David Zueco; Fernando Luis (Communications Materials)
Abstract Waveguide quantum electrodynamics studies interactions of matter with photons traveling via a transmission guide and how these can be exploited to control quantum emitters and to establish quantum correlations between them. Here, we explore the competition between such light-mediated interactions with intrinsic matter-matter interactions. For this, we couple a superconducting line to a magnetic material made of organic free radical molecules. We find that molecules belonging to one of the two crystal sublattices form one-dimensional spin chains. Temperature then controls spin correlations along these chains in a continuous and monotonic way. In the paramagnetic region (T > 0.7 K), the microwave transmission evidences a collective coupling of quasi-identical spins to the propagating photons, with coupling strengths that reach values close to the dissipation rates. As T decreases, the growth of spin correlations, combined with the anisotropy in the spin-spin exchange constants, tend to suppress the collective spin-photon coupling. In this regime, the spin visibility in transmission also reflects a gradual change in the nature of the dominant spin excitations, from single-spin flips to bosonic magnons.